Distinct Effects of Dexamethasone on Human Natural Killer Cell Responses Dependent on Cytokines - Morgan, David J.; Davis, Daniel M. (Frontiers in Immunology, 2017)
Glucocorticoids (GCs) have long been known to be immune suppressive and synthetic variants are widely used in the treatment of inflammatory disorders. Here, we report that, while suppressing the initial production of interferon-γ (IFN-γ), the synthetic GC dexamethasone (Dex) enhances the proliferation and survival of natural killer (NK) cells stimulated with interleukin-2 (IL-2) + interleukin-12 (IL-12). Inhibition of mTOR complex 1 by rapamycin revealed the immunosuppressive activity of Dex was independent from the effect of enhancing NK cell proliferation. In the presence of IL-2 + IL-12, Dex also increased the percentage of NK cells that were CD16+ and DNAM1bright, increased the level of expression of CD94 or NKG2A, and improved mitochondrial function of NK cells. Moreover, NK cells treated with cytokines IL-2 and IL-12 + Dex, followed by a 7-day rest, displayed an increased IFN-γ response upon restimulation. Thus, there is a dichotomic effect of GCs on NK cell function dependent on the local cytokine milieu; the NK cell effector response is initially suppressed, but, dependent on the cytokines present, Dex can also augment the proliferation, survival, and reactivity of human NK cells in a secondary recall response.